2017
DOI: 10.21037/jtd.2017.06.119
|View full text |Cite
|
Sign up to set email alerts
|

The role of video-assisted thoracoscopic surgery for management of symptomatic pleural effusion after coronary artery bypass surgery: a best evidence topic report

Abstract: A best evidence topic in thoracic surgery was written addressing whether video-assisted thoracoscopic surgery (VATS) talc pleurodesis could be justified in patients with pleural effusion (PE) after coronary artery bypass graft (CABG) surgery and no-responded to repeated thoracentesis. Ten papers were identified to answer the question. Of these, two were case-series study including ≥4 patients, 7 retrospective analytical studies, and one observational study but no randomized controlled trial (RCTs) was included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Data on the feasibility and benefits of VATS after cardiac procedures remain scarce. Fiorelli et al 11) performed a systematic review of VATS pleurodesis to manage pleural effusion after coronary bypass surgery, and no-responded to repeated thoracentesis. Fiorelli and colleagues 11) included seven retrospective, two observational studies, and four case series in their systematic review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the feasibility and benefits of VATS after cardiac procedures remain scarce. Fiorelli et al 11) performed a systematic review of VATS pleurodesis to manage pleural effusion after coronary bypass surgery, and no-responded to repeated thoracentesis. Fiorelli and colleagues 11) included seven retrospective, two observational studies, and four case series in their systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…Fiorelli et al 11) performed a systematic review of VATS pleurodesis to manage pleural effusion after coronary bypass surgery, and no-responded to repeated thoracentesis. Fiorelli and colleagues 11) included seven retrospective, two observational studies, and four case series in their systematic review. They concluded that VATS is safe and effective, and its use could help prevent trapped lungs through the resection of adhesions and loculations.…”
Section: Discussionmentioning
confidence: 99%
“…However, some CABG patients develop moderate to severe effusions that sometimes cause symptoms. Major pleural effusions occur in the early postoperatively duration with a frequency of 0.6-8.7% [5][6] . There are 2 types of pleural effusions that are related directly to CABG after surgery: atelectasis effusion due to diaphragmatic dysfunction and haemorrhagic effusion from harvesting of internal mammary artery (IMA).…”
Section: Introductionmentioning
confidence: 99%